Abdominal aortic aneurysm morphology in the Chinese population and endovascular aortic aneurysm repair eligibility - May Yim-Ping Wong; Kei Kwong Wong (Indian Journal of Vascular and Endovascular Surgery, 2023)
Introduction: The current commercial endovascular abdominal aortic stent grafts are designed based on the anatomical data from the Western population. Objective: To investigate the morphological features of abdominal aortic aneurysm (AAA) in a Chinese cohort and its clinical implications. Methods: It was a retrospective, observational study. The preoperative computed tomography angiogram (CTAs) of patients who underwent endovascular aortic aneurysm repair (EVAR) from January 01, 2015 to December 31, 2020, were analyzed. A predefined set of AAA morphological measurements was taken. The eligibility of EVAR with current commercially available stent grafts on the market was examined. Results: A total of 210 cases were studied. The mean AAA diameter was 64.3 mm. The mean proximal and distal neck diameters were 22.9 mm and 24.4 mm, respectively, whereas the mean neck length was 23.8 mm and the mean infra-renal angle was 51.6°. The right and left mean common iliac arteries (CIAs) diameters were 21.2 mm and 18.3 mm. The right and left mean CIA lengths were 35.7 mm and 37.3 mm. The mean external iliac artery (EIA) diameter was 8.3 mm bilaterally. Female gender was associated with significantly smaller neck diameters, smaller EIA diameters, and larger infra-renal angle. EVAR eligibility ranged from 16%–37% and was significantly lower in females. Conclusions: The majority of Chinese patients with AAA did not meet the anatomical eligibility for EVAR, with neck angulation being the major deterrent. Female patients posed an additional anatomical challenge due to larger infra-renal angle and smaller iliac access diameter. The development of low-profile angulated neck-compatible EVAR devices may expand EVAR applicability in future.